2015
DOI: 10.4103/0973-1075.164892
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial evaluating the role of honey in reducing pain due to radiation induced mucositis in head and neck cancer patients

Abstract: Background:There are various drugs tried for relieving pain associated with radiation-induced mucositis. This paper aims to study role of honey in relieving pain due to radiation induced mucositis in head and neck cancer patients receiving concomitant chemoradiation.Materials and Methods:A randomized controlled trial on 78 subjects (40 in test group and 38 in control group) was undertaken to study the analgesic effect of honey, but the analysis of 69 patients was done as nine patients (four in test and five in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 8 publications
2
23
0
3
Order By: Relevance
“…Samdariya et al investigated the role of honey in lessening pain after radiation-induced mucositis in head and neck cancer patients and concluded that honey significantly decreased the severity of mucositis-associated pain and overall radiotherapy treatment duration. Their results are in agreement with those of the present study, indicating that the use of honey diminishes the pain in damaged biological tissues (21). In a case report, Kalrozi indicated that honey dressing improved head injury resulting from trauma and accident and reduced pain in patients, which is consistent with our results (19).…”
Section: Discussionsupporting
confidence: 93%
“…Samdariya et al investigated the role of honey in lessening pain after radiation-induced mucositis in head and neck cancer patients and concluded that honey significantly decreased the severity of mucositis-associated pain and overall radiotherapy treatment duration. Their results are in agreement with those of the present study, indicating that the use of honey diminishes the pain in damaged biological tissues (21). In a case report, Kalrozi indicated that honey dressing improved head injury resulting from trauma and accident and reduced pain in patients, which is consistent with our results (19).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, exposure to fractionated doses of radiation compromises the wound healing process and this aggravates and complicates the situation [ 1 ]. In the present study honey was observed to be effective at mitigating radiation mucositis, which is in agreement to earlier reports [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The observed effects could be attributed to the honey’s analgesic [ 9 , 12 ], antimicrobial [ 12 ], and wound-healing effects [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the recent past, studies from around the world have shown that honey was effective at mitigating radiation- and chemotherapy-induced mucositis [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Met analyses have substantiated the observed beneficial effects [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırma sonucunda uygulamanın, radyoterapi ilişkili oral mukozit ağrısını ha ettiği bildirilmiştir. [60] Diğer güncel bir araştırmada; bal ve kahve karışımının (300 gram bal ve 20 gram hazır kahve ) kemoterapi ilişkili oral mukozit tedavisinde sadece bal (300 gram bal) uygulanan gruba göre daha etkili olduğu bulunmuştur. Araştırmada ağız bakım materyalleri süspansiyon şeklinde hastalara verilmiş ve bir hafta boyunca her 3 saatte bir 10 mililitre solüsyon ile gargara yapıp yutmaları sağlanmıştır.…”
Section: Antioksidan Vitaminlerunclassified